Transforming the representations of preschool-age children regarding geophysical entities and physical geography - MARIA KAMPEZA; KONSTANTINOS RAVANIS (Metaichmio Publications, 2009)
A semi-structured interview was individually administered to 76 preschoolers. The interview raised questions about the conceptual understanding of certain geophysical entities. A teaching intervention designed to attempt an understanding of the relationship between them and earth's surface was implemented with groups of 5-9 children in order to help children construct a more "realistic" model of earth. The intervention's effectiveness was consequently evaluated (after two weeks) using an interview similar to that conducted prior to the intervention. The results of the study indicated that prior to the intervention many children faced difficulties in descriptive understanding of even familiar geographic features, such as rivers, lakes and islands. After the intervention the majority of children readily conceptualized certain aspects of most of the geophysical entities and correlated them with earth's surface. Educational and research implications are discussed.